2018
DOI: 10.1016/j.cognition.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Young infants’ discrimination of subtle phonetic contrasts

Abstract: It is generally accepted that infants initially discriminate native and non-native contrasts and that perceptual reorganization within the first year of life results in decreased discrimination of non-native contrasts, and improved discrimination of native contrasts. However, recent findings from Narayan, Werker, and Beddor (2010) surprisingly suggested that some acoustically subtle native-language contrasts might not be discriminated until the end of the first year of life. We first provide countervailing evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…Sundara et al (), in contrast, reported that young English‐learning infants are in fact able to discriminate the Filipino /n/–/ŋ/ contrast. Given Narayan et al's stimuli, English‐learning 4‐ and 6‐month‐old infants were sensitive to the subtle phonetic differences that distinguish /n/ and /ŋ/; young English‐ and French‐learning monolingual infants could discriminate additional subtle non‐native contrasts.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sundara et al (), in contrast, reported that young English‐learning infants are in fact able to discriminate the Filipino /n/–/ŋ/ contrast. Given Narayan et al's stimuli, English‐learning 4‐ and 6‐month‐old infants were sensitive to the subtle phonetic differences that distinguish /n/ and /ŋ/; young English‐ and French‐learning monolingual infants could discriminate additional subtle non‐native contrasts.…”
Section: Introductionmentioning
confidence: 95%
“…Narayan et al () employed a non‐infant‐controlled version of the habituation task: Stimuli were presented for the same fixed amount of time for all infants regardless of whether the infant looked toward the screen. Sundara et al () instead used an infant‐controlled version of the paradigm: When infants did not look toward the screen (the source of the auditory stimulus), the sounds were terminated. The infant‐controlled version makes it easier for infants to learn the contingencies between looking and the auditory stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the contrast has merged to [n] in some Austronesian languages (e.g., Hawai'ian and Tahitian). Recently, Sundara et al (2018) have challenged the results of Narayan et al (2010). Using exactly the same Filipino nasal tokens from Narayan et al (2010), Sundara et al showed that English-and French-hearing 6-month-olds discriminated the [na]-[ŋa] under a stricter habituation criterion, longer habituation trials, and shorter ISI than used in the original study.…”
Section: Nasal Place Of Articulation: Murmur To Formant Transitionsmentioning
confidence: 99%
“…One possible explanation would be that the 10-12 month period is a necessarily sensitive period in development when the effects of the accumulation of native language exposure become evident. 10 Sundara et al (2018) also showed English-and French-hearing infants' successful discrimination of a dentalretroflex nasal contrast ([na]-[ɳa]). We are unaware of any language which contrasts dental with retroflex nasals in word-initial position (Hamann, 2003).…”
Section: Infant Consonant Perception From An Acoustic Perspective: mentioning
confidence: 99%
See 1 more Smart Citation